HUBUNGAN ANTARA TINGKAT STRES DENGAN STATUS GIZI MAHASISWA TINGKAT AKHIR DI FAKULTAS ILMU KESEHATAN UNIVERSITAS ISLAM AS-SYAFI’IYAH JAKARTA TIMUR TAHUN 2021 - Devita Miliandani; Zuhriya Meilita (Afiat, 2021)
At the end of the lecture period, final year students must complete academic requirements, one of which is writing a thesis. Not infrequently during the thesis preparation process, final year students experience several obstacles and demands. Constraints and demands faced by final year students can be a stressor. This can cause final year students to easily experience stress. Stress can disrupt the body's balance with stress sufferers. One of the body balances that are disturbed due to stress is the body's physiology related to food intake which can affect the nutritional status of students. The purpose of this study was to determine the relationship between stress levels and nutritional status in final year students at the Faculty of Health Sciences, As-Syafi'iyah Islamic University. Methods this study used a descriptive correlative, amount of population at this research is counted 103 students. Samples taken by proportional sampling technique of 79 students. But in this study, only 57 respondents were conducted because the other 22 respondents did not meet the specified inclusion criteria. The analysis used univariate and bivariate using chi-square. Result showed the results of the Chi-Square analysis, the P value = 0.024 ≤ 0.05. Conclusion there is a significant relationship between stress levels and the nutritional status of final year students of FIKes UIA Jakarta. Suggestions for final year students of FIKes UIA are suggested to be able to increase knowledge about stress coping strategies in order to cope with stressors well.